please answer this question fast
Attachments:
![](https://hi-static.z-dn.net/files/d1c/caa156b6dd8b6c2c4a8dca6179129901.jpg)
Answers
Answered by
0
Here is your answer :-
sum of zeroes = alpha + beta
-b/a = alpha + beta
so ,
![\alpha + \beta = \frac{ - b}{a} \alpha + \beta = \frac{ - b}{a}](https://tex.z-dn.net/?f=+%5Calpha+++%2B++%5Cbeta++%3D++%5Cfrac%7B+-+b%7D%7Ba%7D+)
because b = b and a = a
if u like my answer , then pls mark as brainliest
sum of zeroes = alpha + beta
-b/a = alpha + beta
so ,
because b = b and a = a
if u like my answer , then pls mark as brainliest
Similar questions